Thyroid nocardiosis: Case report and review of the literature. Issue 4 (11th March 2021) - Esnault, Violaine; Wittnebel, Sebastian; Pouillon, Mathias; Collarino, Rocco; Jauréguiberry, Stephane; Chachaty, Elisabeth; Gachot, Bertrand; Wyplosz, Benjamin
Abstract: Disseminated nocardiosis is a rare but growing concern in immunocompromised patients. Typical localizations include the lung, brain and/or soft tissues, but laboratory confirmation of nocardiosis usually requires sampling of infected organs by invasive procedures such as bronchoalveolar lavage or brain biopsy. We report a case of disseminated nocardiosis occurring in a hematopoietic stem‐cell transplant recipient, with clinical lung and brain localizations. Examination of the thyroid gland was suggestive of a unilateral abscess. A culture of thyroid pus sampled by fine‐needle aspiration was positive for Nocardia farcinica and therefore avoided a more invasive procedure. The patient recovered after a six‐month antibiotic therapy without thyroid surgery. We reviewed other ten cases of thyroid nocardiosis published in the medical literature. Among the ten cases of disseminated nocardiosis established during the patient's lifetime including ours, six (60%) were asymptomatic and seven (70%) were confirmed by culture of the aspiration of thyroid pus. When disseminated nocardiosis is suspected, systematic examination for a thyroid abscess may help establish a microbiological diagnosis and prevent further invasive procedures.